Evaluation of the mental foramen position in pediatric patients. - Dotto, Sidney Ricardo; Travassos, Rosana Maria Coelho; Médici Filho, Edmundo; Moraes, Luiz Cesar de; Moraes, Mari Eli Lleonelli de; Castilho, Julio Cezar Melo; Porto, Carolina O. T. W.; Dotto, Patrícia P. (Brazilian Dental Science, 2010)
The aim of the present study was to evaluate the location of the mental foramen, using panoramic x-rays from children with ages among ten to 12 years. In a first moment, the radiographs were digitalized and measures were accomplished in the Image Tool 1.27 software, being verified the distance between the mandible border and the mental foramen inferior portion, the total height of the alveolar ridge, and also the distance between the medium portion of the mental foramen and a traced line of the nasal spine previously to a point located in the most inferior portion of the mentus. In children with ages among ten and 11 years, the percentage occurrence of the mental foramen location was in the inferior third of the alveolar ridge and, in the 12 years age group, it was in the medium third. Authors concluded that the position of the mental foramen modifies with the increase of the age, being important the analysis of the precisely location of the mental foramen in Pediatric Dentistry.